Preparation method of anti-ultraviolet aging silicone rubber
By introducing sulfonated silicone polyimide and nano zinc oxide into silicone rubber, the shortcomings of silicone rubber in resistance to UV aging and mechanical properties are solved, and its resistance to UV and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202510172902.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-17
AI Technical Summary
Existing silicone rubber materials have shortcomings in their resistance to UV aging and mechanical properties, especially in terms of tear strength and high temperature resistance.
By polymerizing the phenyl group-containing dinitro compound with dianhydride compound and aromatic diamine compound, silicone polyimide with benzene ring in the side chain, and sulfonated silicone polyimide is generated through concentrated sulfuric acid sulfonated silicone polyimide, and kneading and vulcanizing it with methylvinyl silicone rubber, nano zinc oxide, etc., to prepare a silicone rubber that is resistant to ultraviolet aging.
It improves the resistance to UV aging and mechanical properties of silicone rubber, including improving Shore A hardness, tear strength and thermal decomposition temperature, enhancing the dispersion and compatibility of nano zinc oxide, and significantly improving the resistance to UV of silicone rubber.
Smart Images

Figure BDA0005274566060000021 
Figure BDA0005274566060000031 
Figure BDA0005274566060000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicone rubber, in particular to a method for preparing silicone rubber resistant to ultraviolet aging. Background Art
[0002] Silicone rubber has good high and low temperature resistance, excellent elasticity, high electrical insulation, and strong hydrophobicity. It is widely used in wires and cables, medical equipment, and automobile manufacturing. Adding nanofillers to silicone rubber can improve its mechanical properties and anti-ultraviolet aging properties. Nano zinc oxide is a non-toxic, environmentally friendly, cheap and easily available nano material, and can absorb ultraviolet rays to improve the anti-ultraviolet aging properties of materials such as plastics and rubber. Chinese patent CN116426215B discloses a composite coating and its preparation method, a silicone rubber protective cover and an insulator. The silicone rubber adhesive is used as a coating, and hydrophobically modified four-needle zinc oxide powder and nano metal oxide powder are embedded. The two are used as inorganic ultraviolet shielding agents. The resulting composite coating has good ultraviolet shielding and anti-aging effects. However, the patent does not improve the tear strength and high temperature resistance of silicone rubber. Polyimide has the advantages of high mechanical strength, good high temperature resistance, and excellent insulation performance. It can be used as a structural material or functional material to improve the comprehensive performance of silicone rubber materials. Summary of the invention
[0003] (I) Technical problems to be solved: The present invention provides a method for preparing ultraviolet aging-resistant silicone rubber, which improves the ultraviolet aging resistance and mechanical properties of the silicone rubber.
[0004] (II) Technical solution: A method for preparing a silicone rubber resistant to ultraviolet aging, comprising the following steps:
[0005] Step A, add N,N-dimethylformamide, dianhydride compound, aromatic diamine compound, silicon-containing diamine monomer into a reaction container, stir and react at room temperature in a nitrogen atmosphere for 18-24 hours, pour the solution on the surface of the glass mold, place it in a heating box, heat it to 100-120°C for 1-2 hours, 140-160°C for 1.5-2 hours, 200-220°C for 1-1.5 hours, 240-260°C for 1-1.5 hours, 280-300°C for 1-1.5 hours, cool it, and obtain silicone polyimide.
[0006] Step B: In an ice bath and nitrogen atmosphere, add concentrated sulfuric acid and organosilicon polyimide to a reaction vessel, stir and heat to 40-55° C., carry out sulfonation reaction for 12-18 hours, cool and pour the solution into ice water, filter and wash with water, and dry to obtain sulfonated organosilicon polyimide.
[0007]
[0008] Step C, placing methyl vinyl silicone rubber, sulfonated silicone polyimide, and nano zinc oxide in an open mill for plasticization, then adding an accelerator, an antioxidant, and a crosslinking agent for mixing, and then adding a vulcanizing agent for mixing, and finally vulcanizing the materials in a flat vulcanizer, first at 160-170° C., 10-12MPa pressure for 20-30min, and then at normal pressure, 170-175° C. for 2-3h, cooling and discharging, to obtain UV-resistant silicone rubber.
[0009] Furthermore, in step A, the molar ratio of the dianhydride compound, the aromatic diamine compound, and the silicon-containing diamine monomer is 100:(60-90):(10-40).
[0010] Furthermore, the dianhydride compound is pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride or 4,4'-biphenyl ether dianhydride, and the aromatic diamine compound is p-phenylenediamine, 4,4-biphenyl ether diamine or 4,4'-diaminodiphenylmethane.
[0011] Further, the preparation method of the silicon-containing diamine monomer is:
[0012] (1) Add ethanol, sodium ethoxide in a molar ratio of (2-2.2)::1:(2.2-2.6), 1,3-bis(3-chloropropyl)-1,1,3,3-tetramethyldisiloxane, and 4-nitrodiphenylamine into a reaction vessel, heat to 70-80° C., condense and reflux for 4-6 hours, cool and filter, distill the filtrate under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a silicon-containing dinitro monomer.
[0013] (2) Add ethanol to the reaction vessel, introduce nitrogen, add silicon-containing dinitro monomer, palladium carbon catalyst, and hydrazine hydrate in a mass ratio of 100:(5.8-6.6):(32-42), heat to 70-80°C, condense and reflux for 6-8h, filter and distill the filtrate under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a silicon-containing diamine monomer. The reaction formula is:
[0014]
[0015] Furthermore, in step C, the mass ratio of methyl vinyl silicone rubber, sulfonated silicone polyimide and nano zinc oxide is 100:(15-30):(2-8).
[0016] Furthermore, the accelerator is 2-mercaptobenzothiazole, the antioxidant is N-phenyl-2-naphthylamine, the crosslinking agent is diisopropylbenzene peroxide, and the vulcanizing agent is sulfur.
[0017] (III) Technical effect of the present invention: a silicon-containing dinitro compound containing phenyl is polymerized with a dianhydride compound and an aromatic diamine compound to obtain an organosilicon polyimide containing a benzene ring in the side chain, and then the side chain benzene ring is sulfonated with concentrated sulfuric acid to obtain a sulfonated organosilicon polyimide with a higher sulfonic acid content, and then mixed with methyl vinyl silicone rubber, nano zinc oxide, an antioxidant, a vulcanizing agent, etc., and vulcanized to obtain a silicone rubber resistant to ultraviolet aging.
[0018] The sulfonated organosilicon polyimide of the present invention contains the same siloxane structure as methyl vinyl silicone rubber, improves its compatibility with silicone rubber, is beneficial to improving the Shore A hardness, tear strength and thermal decomposition temperature of silicone rubber, and has higher mechanical properties and high temperature resistance.
[0019] The side chain of the organosilicon polyimide of the invention contains a large number of sulfonic acid groups, which can interact with the surface of nano zinc oxide and be coated on the surface of nano zinc oxide, thereby reducing the agglomeration of nano zinc oxide and improving the compatibility between nano zinc oxide and silicone rubber. The uniformly dispersed nano zinc oxide has an excellent reinforcing effect and improves the anti-ultraviolet performance of silicone rubber. After anti-ultraviolet aging tests, the Shore A hardness and tear strength of the silicone rubber decrease slightly and have a high retention rate. DETAILED DESCRIPTION
[0020] In order to facilitate those skilled in the art to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific examples, but the present invention is not limited thereto. Palladium carbon catalyst: Product No. YB54681, CAS No.: 7440-05-3, Hunan Yunbang Biotechnology Co., Ltd. Concentrated sulfuric acid: concentration 98.3wt%.
[0021] Example 1: (1) Add 200 mL of ethanol, 60 mmol of sodium ethoxide, 30 mmol of 1,3-di(3-chloropropyl)-1,1,3,3-tetramethyldisiloxane and 66 mmol of 4-nitrodiphenylamine into a reaction vessel, heat to 80°C, condense and reflux for 4 hours, cool and filter, distill the filtrate under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a silicon-containing dinitro monomer.
[0022] (2) Add 120 mL of ethanol to a reaction container, introduce nitrogen, add 10 g of a silicon-containing dinitro monomer, 0.66 g of a palladium-carbon catalyst, and 3.2 g of 80% by mass hydrazine hydrate, heat to 80° C., condense and reflux for 6 h, filter, and distill the filtrate under reduced pressure. After washing with water, the product is recrystallized in ethanol to obtain a silicon-containing diamine monomer.
[0023] (3) Add 250 mL of N,N-dimethylformamide, 100 mmol of 4,4'-biphenyl ether dianhydride, 90 mmol of p-phenylenediamine, and 10 mmol of silicon-containing diamine monomer into a reaction container, stir and react at room temperature for 18 h in a nitrogen atmosphere, pour the solution on the surface of a glass mold, place it in a heating box, heat it to 100° C. for 2 h, 140° C. for 2 h, 200° C. for 1.5 h, 260° C. for 1 h, and 300° C. for 1 h, and cool it to obtain silicone polyimide.
[0024] (4) In an ice bath and under a nitrogen atmosphere, 800 mL of concentrated sulfuric acid and 50 g of organosilicon polyimide were added to a reaction container, and the mixture was heated to 45° C. after stirring to carry out a sulfonation reaction for 18 h. After cooling, the solution was poured into ice water, filtered, washed with water, and dried to obtain a sulfonated organosilicon polyimide.
[0025] (5) 1 kg of methyl vinyl silicone rubber, 150 g of sulfonated silicone polyimide, and 20 g of nano zinc oxide (average particle size 30 nm) were placed in an open mill and plasticized for 40 min, and then 20 g of accelerator 2-mercaptobenzothiazole, 16 g of antioxidant N-phenyl-2-naphthylamine, and 22 g of cross-linking agent diisopropyl peroxide were added and mixed for 40 min, and then 12 g of vulcanizing agent sulfur was added and mixed for 10 min. Finally, the material was vulcanized in a flat vulcanizer at 170° C. and 10 MPa pressure for 20 min, and then vulcanized at 175° C. for 2 h at normal pressure, and cooled to obtain UV-resistant silicone rubber.
[0026] Example 2: (1) Add 250 mL of ethanol, 66 mmol of sodium ethoxide, 30 mmol of 1,3-di(3-chloropropyl)-1,1,3,3-tetramethyldisiloxane and 72 mmol of 4-nitrodiphenylamine into a reaction vessel, heat to 75°C, condense and reflux for 6 hours, cool and filter, distill the filtrate under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a silicon-containing dinitro monomer.
[0027] (2) Add 120 mL of ethanol to a reaction container, introduce nitrogen, add 10 g of a silicon-containing dinitro monomer, 0.58 g of a palladium-carbon catalyst, and 4.2 g of 80% by mass hydrazine hydrate, heat to 70° C., condense and reflux for 6 h, filter, and distill the filtrate under reduced pressure. After washing with water, the product is recrystallized in ethanol to obtain a silicon-containing diamine monomer.
[0028] (3) Add 300 mL of N,N-dimethylformamide, 100 mmol of pyromellitic anhydride, 75 mmol of 4,4-biphenyl ether diamine, and 25 mmol of silicon-containing diamine monomer into a reaction container, stir and react at room temperature for 24 hours in a nitrogen atmosphere, pour the solution on the surface of a glass mold, place it in a heating box, heat it to 100° C. for 2 hours, 160° C. for 1.5 hours, 220° C. for 1 hour, 260° C. for 1 hour, and 280° C. for 1 hour, cool it, and obtain silicone polyimide.
[0029] (4) In an ice bath and under a nitrogen atmosphere, 800 mL of concentrated sulfuric acid and 50 g of organosilicon polyimide were added to a reaction container, and the mixture was heated to 55° C. after stirring to carry out a sulfonation reaction for 12 h. After cooling, the solution was poured into ice water, filtered, washed with water, and dried to obtain a sulfonated organosilicon polyimide.
[0030] (5) 1 kg of methyl vinyl silicone rubber, 220 g of sulfonated silicone polyimide, and 50 g of nano zinc oxide (average particle size 30 nm) were placed in an open mill and plasticized for 60 min, and then 18 g of accelerator 2-mercaptobenzothiazole, 13 g of antioxidant N-phenyl-2-naphthylamine, and 24 g of cross-linking agent diisopropyl peroxide were added and mixed for 40 min, and then 8 g of vulcanizing agent sulfur was added and mixed for 10 min. Finally, the material was vulcanized in a flat vulcanizer at 160° C. and 12 MPa pressure for 30 min, and then vulcanized at 170° C. for 3 h at normal pressure, and cooled to obtain UV-resistant silicone rubber.
[0031] Example 3: (1) Add 250 mL of ethanol, 66 mmol of sodium ethoxide, 30 mmol of 1,3-di(3-chloropropyl)-1,1,3,3-tetramethyldisiloxane and 78 mmol of 4-nitrodiphenylamine into a reaction vessel, heat to 70°C, condense and reflux for 6 hours, cool and filter, distill the filtrate under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a silicon-containing dinitro monomer.
[0032] (2) Add 150 mL of ethanol to a reaction container, introduce nitrogen, add 10 g of a silicon-containing dinitro monomer, 0.64 g of a palladium-carbon catalyst, and 3.8 g of 80% by mass hydrazine hydrate, heat to 75° C., condense and reflux for 8 h, filter, and distill the filtrate under reduced pressure. After washing with water, the product is recrystallized in ethanol to obtain a silicon-containing diamine monomer.
[0033] (3) Add 300 mL of N,N-dimethylformamide, 100 mmol of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 60 mmol of 4,4'-diaminodiphenylmethane, and 40 mmol of silicon-containing diamine monomer into a reaction container, stir and react at room temperature for 24 h in a nitrogen atmosphere, pour the solution on the surface of a glass mold, place it in a heating box, heat it to 120° C. for 1 h, 150° C. for 2 h, 200° C. for 1.5 h, 240° C. for 1.5 h, and 280° C. for 1.5 h, cool it, and obtain silicone polyimide.
[0034] (4) In an ice bath and under a nitrogen atmosphere, 800 mL of concentrated sulfuric acid and 50 g of organosilicon polyimide were added to a reaction vessel, and the mixture was heated to 40° C. after stirring to carry out a sulfonation reaction for 18 h. After cooling, the solution was poured into ice water, filtered, washed with water, and dried to obtain a sulfonated organosilicon polyimide.
[0035] (5) 1 kg of methyl vinyl silicone rubber, 300 g of sulfonated silicone polyimide, and 80 g of nano zinc oxide (average particle size 30 nm) were placed in an open mill for plasticizing for 60 min, and then 22 g of accelerator 2-mercaptobenzothiazole, 18 g of antioxidant N-phenyl-2-naphthylamine, and 20 g of cross-linking agent diisopropyl peroxide were added and mixed for 40 min, and then 12 g of vulcanizing agent sulfur was added and mixed for 10 min. Finally, the material was vulcanized in a flat vulcanizer at 160° C. and 10 MPa pressure for 30 min, and then vulcanized at 170° C. for 3 h at normal pressure, and cooled to obtain UV-resistant silicone rubber.
[0036] The difference between Comparative Example 1 and Example 1 is that no sulfonated silicone polyimide is added.
[0037] (1) 1 kg of methyl vinyl silicone rubber and 20 g of nano zinc oxide (average particle size 30 nm) were placed in an open mill for plasticizing for 40 min, and then 20 g of accelerator 2-mercaptobenzothiazole, 16 g of antioxidant N-phenyl-2-naphthylamine, and 22 g of cross-linking agent diisopropylbenzene peroxide were added and mixed for 40 min. Then 12 g of vulcanizing agent sulfur was added and mixed for 10 min. Finally, the material was vulcanized in a flat vulcanizer at 170° C. and 10 MPa pressure for 20 min, and then vulcanized at 175° C. for 2 h at normal pressure, and cooled to obtain UV-resistant silicone rubber.
[0038] The difference between Comparative Example 2 and Example 1 is that silicone polyimide is used instead of sulfonated silicone polyimide.
[0039] (1) 1 kg of methyl vinyl silicone rubber, 150 g of silicone polyimide, and 20 g of nano zinc oxide (average particle size 30 nm) were placed in an open mill and plasticized for 40 min, and then 20 g of accelerator 2-mercaptobenzothiazole, 16 g of antioxidant N-phenyl-2-naphthylamine, and 22 g of cross-linking agent diisopropylbenzene peroxide were added and mixed for 40 min, and then 12 g of vulcanizing agent sulfur was added and mixed for 10 min. Finally, the material was vulcanized in a flat vulcanizer at 170° C. and 10 MPa pressure for 20 min, and then vulcanized at 175° C. for 2 h at normal pressure, and cooled and discharged to obtain UV-resistant silicone rubber.
[0040] The difference between Comparative Example 3 and Example 1 is that when preparing the polyimide, no silicon-containing diamine monomer is added.
[0041] (1) Add 250 mL of N,N-dimethylformamide, 100 mmol of 4,4'-biphenyl ether dianhydride, and 100 mmol of p-phenylenediamine into a reaction container, stir and react at room temperature for 18 h in a nitrogen atmosphere, pour the solution onto the surface of a glass mold, place it in a heating box, heat it to 100° C. for 2 h, 140° C. for 2 h, 200° C. for 1.5 h, 260° C. for 1 h, and 300° C. for 1 h, and cool it to obtain polyimide.
[0042] (2) In an ice bath and under a nitrogen atmosphere, 800 mL of concentrated sulfuric acid and 50 g of polyimide were added to a reaction container, and the mixture was heated to 45° C. after stirring to carry out a sulfonation reaction for 18 h. After cooling, the solution was poured into ice water, filtered, washed with water, and dried to obtain a sulfonated polyimide.
[0043] (3) 1 kg of methyl vinyl silicone rubber, 150 g of sulfonated polyimide, and 20 g of nano zinc oxide (average particle size 30 nm) were placed in an open mill and plasticized for 40 min, and then 20 g of accelerator 2-mercaptobenzothiazole, 16 g of antioxidant N-phenyl-2-naphthylamine, and 22 g of cross-linking agent diisopropyl peroxide were added and mixed for 40 min, and then 12 g of vulcanizing agent sulfur was added and mixed for 10 min. Finally, the material was vulcanized in a flat vulcanizer at 170° C. and 10 MPa pressure for 20 min, and then vulcanized at 175° C. for 2 h at normal pressure, and cooled to obtain UV-resistant silicone rubber.
[0044] The difference between Comparative Example 4 and Example 1 is that when preparing polyimide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is used instead of the silicon-containing diamine monomer.
[0045] (1) Add 250 mL of N,N-dimethylformamide, 100 mmol of 4,4'-biphenyl ether dianhydride, 90 mmol of p-phenylenediamine, and 10 mmol of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane into a reaction container, stir and react for 18 h at room temperature in a nitrogen atmosphere, pour the solution onto the surface of a glass mold, place it in a heating box, heat it to 100° C. for 2 h, 140° C. for 2 h, 200° C. for 1.5 h, 260° C. for 1 h, and 300° C. for 1 h, and cool it to obtain a silicone polyimide.
[0046] (2) In an ice bath and under a nitrogen atmosphere, 800 mL of concentrated sulfuric acid and 50 g of organosilicon polyimide were added to a reaction container, and the mixture was heated to 45° C. after stirring to carry out a sulfonation reaction for 18 h. After cooling, the solution was poured into ice water, filtered, washed with water, and dried to obtain a sulfonated organosilicon polyimide.
[0047] (3) 1 kg of methyl vinyl silicone rubber, 150 g of sulfonated silicone polyimide, and 20 g of nano zinc oxide (average particle size 30 nm) were placed in an open mill and plasticized for 40 min, and then 20 g of accelerator 2-mercaptobenzothiazole, 16 g of antioxidant N-phenyl-2-naphthylamine, and 22 g of cross-linking agent diisopropyl peroxide were added and mixed for 40 min, and then 12 g of vulcanizing agent sulfur was added and mixed for 10 min. Finally, the material was vulcanized in a flat vulcanizer at 170° C. and 10 MPa pressure for 20 min, and then vulcanized at 175° C. for 2 h at normal pressure, and cooled to obtain UV-resistant silicone rubber.
[0048] The sulfonated polyimide was dried, weighed, placed in 50 mL of 3 mol / L sodium chloride solution, stirred for 48 h, and H + with Na + After sufficient exchange, the filtrate is filtered and titrated with 5 mmol / L sodium hydroxide solution using phenolphthalein as an indicator until the solution turns red, and the acidity value W is calculated. The larger the acidity value, the higher the sulfonic acid content.
[0049] W = (C x V) / M, C is the concentration of the sodium hydroxide solution, is the titration volume of the sodium hydroxide solution, and M is the mass of the sulfonated polyimide.
[0050] Table 1 Acidity value test
[0051] Acidity value (mmol / L) Example 1 0.82 Example 2 1.16 Example 3 1.37 Comparative Example 3 0.66 Comparative Example 4 0.58
[0052] It can be seen from Table 1 that, compared with Comparative Examples 3 and 4, the polyimide side chains of Examples 1-3 contain a benzene ring structure, which is easy to undergo sulfonation reaction with concentrated sulfuric acid, thereby generating more sulfonic acid groups.
[0053] The Shore A hardness of silicone rubber composite materials was tested according to the national standard GB / T 531.1-2008. The tearing performance was tested according to the national standard GB / T529-2008.
[0054] The silicone rubber was placed in a UV aging test box and subjected to a UV aging test for 1440 hours. The main wavelength of the UV lamp was 340 nm and the total power of the UV lamp was 320 W. The Shore A hardness and tear properties were then tested.
[0055] Weigh 5 mg of the modified silicone rubber composite material and place it in a thermogravimetric analyzer for thermogravimetric performance analysis in a nitrogen atmosphere at a heating rate of 10°C / min.
[0056] Table 2 Silicone rubber performance test.
[0057]
[0058] Compared with Comparative Example 1, sulfonated organosilicon polyimide is added to the silicone rubber of Examples 1-3. The polyimide contains the same siloxane structure as methyl vinyl silicone rubber, which improves its compatibility with silicone rubber, is conducive to improving the Shore A hardness, tear strength and thermal decomposition temperature of silicone rubber, and has higher mechanical properties and high temperature resistance. At the same time, the side chain of organosilicon polyimide contains a large number of sulfonic acid groups, which can interact with the surface of nano zinc oxide, and is coated on the surface of nano zinc oxide, reducing the agglomeration of nano zinc oxide, and improving the compatibility between nano zinc oxide and silicone rubber. The uniformly dispersed nano zinc oxide has an excellent reinforcing effect, and at the same time improves the anti-ultraviolet performance of silicone rubber. After the anti-ultraviolet aging test, the Shore A hardness and tear strength of silicone rubber decrease slightly, and the retention rate is high.
[0059] Compared with Example 1, Comparative Example 2 uses silicone polyimide instead of sulfonated silicone polyimide. The silicone polyimide has good compatibility with silicone rubber and can improve its Shore A hardness, tear strength and thermal decomposition temperature. However, silicone polyimide does not contain sulfonic acid groups, cannot interact with nano zinc oxide, cannot be coated on the surface of nano zinc oxide, does not reduce the agglomeration of nano zinc oxide, and is difficult to improve the compatibility between nano zinc oxide and silicone rubber, resulting in the Shore A hardness and tear strength of silicone rubber being lower than those in Example 1. The dispersibility of nano zinc oxide in the silicone rubber matrix is poor, and its anti-ultraviolet aging performance cannot be well improved. After the anti-ultraviolet aging test, the Shore A hardness and tear strength of silicone rubber decreased greatly, and the retention rate was low.
[0060] In comparative example 3, silicon-containing diamine monomer was not added when preparing polyimide. Polyimide does not contain siloxane structure and has poor compatibility with methyl vinyl silicone rubber, resulting in low Shore A hardness and tear strength of silicone rubber, poor dispersion of nano zinc oxide in silicone rubber matrix, and poor improvement of its anti-ultraviolet aging performance. After anti-ultraviolet aging test, the Shore A hardness and tear strength of silicone rubber decreased greatly and the retention rate was low.
[0061] Comparative Example 4: When preparing polyimide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is used instead of the silicon-containing diamine monomer. The obtained organosilicon polyimide does not contain side chain phenyl, has a low content of sulfonic acid groups after sulfonation, and has a low surface interaction force with nano zinc oxide, resulting in poor compatibility and dispersibility between nano zinc oxide and silicone rubber, and the Shore A hardness, tear strength and UV aging resistance of the silicone rubber are lower than those of Example 1.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing ultraviolet aging resistant silicone rubber, characterized in that: The preparation method comprises the following steps: Step A, adding N,N-dimethylformamide, dianhydride compound, aromatic diamine compound, and the structural formula The silicon-containing diamine monomer is reacted under stirring at room temperature in a nitrogen atmosphere for 18-24 hours, the solution is poured on the surface of a glass mold, placed in a heating box, and heated to 100-120°C for 1-2 hours, 140-160°C for 1.5-2 hours, 200-220°C for 1-1.5 hours, 240-260°C for 1-1.5 hours, and 280-300°C for 1-1.5 hours, and cooled to obtain an organosilicon polyimide; Step B, in an ice bath and under a nitrogen atmosphere, adding concentrated sulfuric acid and organosilicon polyimide to a reaction container, stirring to carry out a sulfonation reaction, and after cooling, pouring the solution into ice water, filtering, washing with water, and drying to obtain a sulfonated organosilicon polyimide; Step C, placing methyl vinyl silicone rubber, sulfonated silicone polyimide, and nano zinc oxide in an open mill for plasticization, then adding an accelerator, an antioxidant, and a crosslinking agent for mixing, then adding a vulcanizing agent for mixing, and finally performing a second-stage vulcanization of the material in a flat vulcanizer, cooling and discharging the material to obtain a silicone rubber that is resistant to ultraviolet aging.
2. The method for preparing the UV-resistant silicone rubber according to claim 1, characterized in that: In the step A, the molar ratio of the dianhydride compound, the aromatic diamine compound, and the silicon-containing diamine monomer is 100:(60-90):(10-40).
3. The method for preparing the UV-resistant silicone rubber according to claim 2, characterized in that: The dianhydride compound is pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride or 4,4'-biphenyl ether dianhydride, and the aromatic diamine compound is p-phenylenediamine, 4,4-biphenyl ether diamine or 4,4'-diaminodiphenylmethane.
4. The method for preparing the UV-resistant silicone rubber according to claim 2, characterized in that: The preparation method of the silicon-containing diamine monomer is: (1) Add ethanol, sodium ethoxide, 1,3-bis(3-chloropropyl)-1,1,3,3-tetramethyldisiloxane and 4-nitrodiphenylamine to a reaction vessel, heat to 70-80° C., condense and reflux for 4-6 hours, cool and filter, distill the filtrate under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a silicon-containing dinitro monomer; (2) Add ethanol to the reaction vessel, introduce nitrogen, add silicon-containing dinitro monomer, palladium carbon catalyst, hydrazine hydrate, heat to 70-80° C., condense and reflux for 6-8 hours, filter, distill the filtrate under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a silicon-containing diamine monomer.
5. The method for preparing the UV-resistant silicone rubber according to claim 5, characterized in that: The molar ratio of sodium ethoxide, 1,3-bis(3-chloropropyl)-1,1,3,3-tetramethyldisiloxane and 4-nitrodiphenylamine in (1) is (2-2.2):1:(2.2-2.6).
6. The method for preparing the UV-resistant silicone rubber according to claim 5, characterized in that: The mass ratio of the silicon-containing dinitro compound, palladium-carbon catalyst and hydrazine hydrate in (2) is 100:(5.8-6.6):(32-42).
7. The method for preparing the UV-resistant silicone rubber according to claim 1, characterized in that: The temperature of the sulfonation reaction in step B is 40-55° C., and the reaction time is 12-18 hours.
8. The method for preparing the UV-resistant silicone rubber according to claim 1, characterized in that: In the step C, the mass ratio of methyl vinyl silicone rubber, sulfonated silicone polyimide and nano zinc oxide is 100:(15-30):(2-8).
9. The method for preparing the ultraviolet aging resistant silicone rubber according to claim 1, characterized in that: The two-stage vulcanization in step C is first vulcanization at 160-170° C. and 10-12 MPa pressure for 20-30 minutes, and then vulcanization at 170-175° C. under normal pressure for 2-3 hours.
10. The method for preparing the UV-resistant silicone rubber according to claim 1, characterized in that: In the step C, the accelerator is 2-mercaptobenzothiazole, the antioxidant is N-phenyl-2-naphthylamine, the crosslinking agent is diisopropylbenzene peroxide, and the vulcanizing agent is sulfur.
Citation Information
Patent Citations
Composite coating and preparation method thereof, silicone rubber protective sleeve and insulator
CN116426215B
Segmented copolymer of side chain sulfonated type polyimide and sulfonated polybutadiene and preparation method thereof
CN101701071A
Modified polyimide resin, adhesive composition containing modified polyimide resin and covering film containing adhesive composition
CN103483586A
Modified TPE insulating material for high-flame-retardance and high-wear-resistance automobile wire harnesses and preparation method of modified TPE insulating material
CN105400114A
Polyimide film and preparation method thereof
CN105461923A
Cited By
High-temperature-resistant mixed silicone rubber and preparation method thereof
CN120442061A
Ageing-resistant overhead insulated cable
CN120527063A
Aging-resistant overhead insulated cable
CN120527063B